Increasing Learning Achievement in Islamic Religious Education Through a Contextual Learning Approach of Students - Daabi, Muhammad Kholif Ikhda; Inayati, Nurul Latifatul (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The background in this study is the low achievement of learning Islamic religious education. This research is intended to improve the learning achievement of Islamic religious education through a contextual learning approach. This exploration uses classroom action research (PTK) which consists of two cycles with four stages, namely, planning, action, observation, and reflection. The subjects of this study were grade XI students of SMA 5 Surakarta consisting of 11 boys and 19 girls. The conclusion of this study is that there is an increase in each cycle. In the first cycle, the average score of the test was 65.17 out of 30 students who took the test, with 37% (11 students) in the complete category and 63% (19 students) in the incomplete category. Furthermore, in cycle II there was an increase in tests with an average of 77.47 out of 30 students who took the test. With many 87% (26 students) completed and 13% (4 students) incomplete. The increase in Islamic Religious Education learning achievement from cycle I to cycle II by 50%. With the contextual learning approach, it can improve the learning achievement of Islamic Religious Education in students.